2021
DOI: 10.1039/d1tc01562a
|View full text |Cite
|
Sign up to set email alerts
|

Study of configuration differentia and highly efficient deep-red thermally activated delayed fluorescent organic light-emitting diodes based on phenanthro[4,5-fgh]quinoxaline derivatives

Abstract: The development of efficient thermally activated delayed fluorescence (TADF) materials with a deep-red emission (emission wavelength beyond 620 nm) remains a great challenge in the field of organic light-emitting diodes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Much work has been carried out to discover chemical motifs that minimize the DE ST gap, and correspondingly maximize rISC. [11][12][13][14][15][16] As a result of this multidisciplinary work, generic design rules for successful TADF emitters have emerged. 17 Primarily, bridging of sterically hindered electron donor (D) and acceptor (A) groups in a twisted D-A architecture commonly results in weakly overlapping highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO).…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been carried out to discover chemical motifs that minimize the DE ST gap, and correspondingly maximize rISC. [11][12][13][14][15][16] As a result of this multidisciplinary work, generic design rules for successful TADF emitters have emerged. 17 Primarily, bridging of sterically hindered electron donor (D) and acceptor (A) groups in a twisted D-A architecture commonly results in weakly overlapping highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO).…”
Section: Introductionmentioning
confidence: 99%
“…26–29 On the other hand, the Φ PL s of red/NIR TADF materials tend to decrease dramatically as the emission wavelength increases because of the energy gap law. 30–36 Therefore, fulfilling the requirements of small Δ E ST and high Φ PL simultaneously is a challenge for red/NIR TADF emitters. 37–41…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] On the other hand, the F PL s of red/NIR TADF materials tend to decrease dramatically as the emission wavelength increases because of the energy gap law. [30][31][32][33][34][35][36] Therefore, fulfilling the requirements of small DE ST and high F PL simultaneously is a challenge for red/NIR TADF emitters. [37][38][39][40][41] There are already several strategies to develop efficient red/ NIR TADF materials for application in OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33] Among the available electron-withdrawing acceptor units, dipyrido[3,2a:2,3-c]phenazine (DPPZ) has been investigated for the design of highly efficient red TADF emitters because of its rigid and fully conjugated planar heteroaromatic structure. [34][35][36][37] Recently, it was demonstrated that the PLQYs of the red TADF emitters can vary significantly according to the donor substitution pattern on planar and rigid acceptors, such as phenanthro[4,5-fgh]quinoxaline-10,11-benzene 38,39 and dibenzo[a,c]phenazine. 40 According to the energy gap law, the PLQY of TADF emitters decreases as their emission wavelength shifts toward the deep-red/near infrared region.…”
Section: Introductionmentioning
confidence: 99%